HESPERIA REleASE+: Improving Solar Proton Event Forecasting by Means of Automated Recognition of Type‐III Radio Bursts - Arik Posner; Olga Ε. Malandraki; Michalis Karavolos; Kostas Tziotziou; Fanis Smanis; Bernd Heber; Henrik Dröge; Patrick Kühl; Giorgos P. Veldes (Space Weather)
Abstract This work reports on an attempt toward improving the Relativistic Electron Alert System for Exploration (REleASE): the occurrence of a type‐III radio burst as a precondition for a REleASE forecast. REleASE forecasts are based on the detection of early arrival of near‐relativistic electrons ahead of more hazardous protons from Solar Energetic Particle (SEP) events. The goal is to allow astronauts on a Lunar or Mars mission sufficient advance warning to reach a radiation shelter to minimize radiation dose exposure. We test a new system that sets a condition of the occurrence of a type‐III radio burst, thus adding independent evidence of particle escape from the Sun, with the aim of reducing known sources of false‐alarms of the existing REleASE system. The High Energy Solar Particle Events foRecastIng and Analysis (HESPERIA) REleASE+ system, which takes advantage of availability of real‐time solar radio observations during the passage of STEREO‐A by Earth in 2023, has now been incorporated in the HESPERIA framework. We discuss the techniques used for automatic detection of type‐III radio bursts preparing for its real‐time implementation, the determination of selection criteria for type‐III bursts that are candidates for solar proton events in the Earth‐moon system, and first results of the combined system.